Expansion during PCR of short single-stranded DNA fragments carrying nonselfcomplementary dinucleotide or trinucleotide repeats - Reichová, Nad'a; Kypr, Jaroslav (Molecular biology reports, 2003)
We performed PCR of many DNA fragments of 6-32 nucleotides in length. Some of the fragments expanded into kilobase lengths even in the absence of the complementary strand. The dramatic expansion was observed for (CA)8, (TG)8, (CA)4, (CA)6, (CA)12, (TG)4, (TG)6, (TG)12, (TC)10, (GA)10 and other single strands. Similar expansions were exhibited by related trinucleotide repeats (TTG)5, (CAA)5, (TGG)5, and (CCA)5 as well. However even small perturbations of the strict repetitive nature of the DNA primary structure substantially reduced the expansions. The expansion products had properties characteristic for normal Watson-Crick duplexes. Hence either the Taq polymerase and/or other components of the PCR buffer promote homoduplex formation of the nonselfcomplementary fragments, which is necessary to prime the synthesis of the complementary DNA strand, or the Taq polymerase is able to copy the single-stranded DNA template without any priming effect. The present observations have implications for the evolution of genomic DNA, microsatellite length polymorphism as well as the pathological expansions of trinucleotide repeats in the human genome.
Keywords: dinukleotidové repetice; DNA Repeat Expansion; párování bází; Humans; sekvence nukleotidů; Temperature; DNA, Single-Stranded; teplota; trinukleotidové repetice; Base Pairing; lidé; expanze repetic DNA; jednovláknová DNA; mutageneze; Base Sequence; Mutagenesis; polymerázová řetězová reakce; Dinucleotide Repeats; Polymerase Chain Reaction; Nucleic Acid Hybridization; hybridizace nukleových kyselin; Trinucleotide Repeats